Antibiotic susceptibility of Streptococcus pneumoniae in nasopharyngeal carriers in healthy children younger than one year of age in Lima, Perú - Velásquez Orellano, Edgar R. (2008)
Introducction: Pneumococcus is a major cause of morbidity and mortality in children in developing countries. Over the last few years, pneumococcal strains resistant to penicillin and other antibiotics commonly used in pediatrics have emerged. There are few recent local studies that describe this problem.Objectives: The main purpose of the study was to determine the pneumococcal resistance rates in healthy nasopharyngeal carriers 2 to 12 months of age, who attended the outpatient clinic for a routine well child and/ or vaccination visit at Cayetano Heredia, Edgardo Rebagliati, San Bartolomé Hospitals and Instituto Nacional de Salud del Niño in Lima-Peru.Methods: Nasopharyngeal samples were obtained from 400 children (November 2007-June 2008) for S. pneumoniae culture and determination of the susceptibility to penicillin and other antibiotics by disk diffusion.Results: The pneumococcal carriage rate was 28% (111/400). From the 111 strains isolated, 60 (55%) were resistant to cotrimoxazole, 52 (47%) to penicillin and 30 (35%) to azythromycin. We did not find any association between the factors analyzed and the carrier state and / or antibiotic resistance.Conlusions: We found high resistance rates of pneumococcus to cotrimoxazole and penicillin. However, this study needs to be complemented with minimal inhibitory concentrations in order to use the new penicillin breakpoints for non-meningeal strains. With the new break points, it is likely that penicillin will continue to be the drug of choice for non-severe infections outside the central nervous system.